Mantra Atharwa Veda sebagai Kedamaian dan Pencegah Penderitaan dalam Kehidupan Manusia - Ni Ketut Puspita Sari; I Nyoman Mandiasa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The Vedas which are the most important scriptures in Hinduism contain a collection of revelations which are compiled and systematically rearranged according to their purpose. All the Vedas referred to as the Samhita and Sruti Mantra comprise four groups or the Chess of the Vedic Samhita. The sruti means revelation, Samhita which means set. The four groups (samhita) are: Rg Veda, Yajna Veda, Sama Veda and Atharwa Veda, three of the four groups of Vedas are called Tri Widya or Vedic Trayi, so Atharwa Veda is classified as the fourth or final Veda, traditionally the Atharwa Veda is recognized as the Hindu scripture of the Hindu religion. included in the sruti Veda (Sruti Veda). Atharwa Veda contains things that are commonly known by the people or people and not so with the contents of the Rg Veda its contents are more secular compared to other Vedas that specialize in teaching about religious worship, Atharwa Veda teachings mainly teach how people can overcome the peace that results in division and suffering in human life, many interpreted to contain wisdom about worldly life while the way of worship is not a basic creed.